2011
DOI: 10.1097/01.sa.0000407045.50521.3f
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Nonagenarians Undergoing Emergency, Non-Trauma Surgery

Abstract: almost 3-fold longer than in younger patients. Nonetheless, even in older patients, reversal with sugammadex does not have to be delayed until the second twitch of the TOF response appears or spontaneous respiration is detected, as is the case with neostigmine.There are likely explanations for the longer recovery time in geriatric patients. The onset of action of injected sugammadex is likely dependent on cardiac output and muscle blood flow. Particularly in women, cardiac output decreases moderately with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Outcome data were significantly worse for older patients, with a fifth of patients failing to leave hospital alive, although it should be noted that ∼82% of 79 ‘extremely old’ patients (> 85 years of age) survived to hospital discharge. Unsurprisingly, given the physiological decline and co‐morbid pathology associated with age, recovery from surgery appeared to be slower in older patients, resulting in longer inpatient stay (similar to findings of previous studies [18, 19]) and financial cost.…”
Section: Discussionsupporting
confidence: 81%
“…Outcome data were significantly worse for older patients, with a fifth of patients failing to leave hospital alive, although it should be noted that ∼82% of 79 ‘extremely old’ patients (> 85 years of age) survived to hospital discharge. Unsurprisingly, given the physiological decline and co‐morbid pathology associated with age, recovery from surgery appeared to be slower in older patients, resulting in longer inpatient stay (similar to findings of previous studies [18, 19]) and financial cost.…”
Section: Discussionsupporting
confidence: 81%
“…The statistical analysis was performed with SPSS 15.0 (SPSS Inc., Chicago, IL, USA). To determine the sample size, we assumed an expected TR of 0·34, based on our preliminary descriptive demographic study of this population (Pelavski et al ., ). As a result, 135 patients yielded a confidence level of 95% and a precision of 8%.…”
Section: Methodsmentioning
confidence: 97%
“…Our in-hospital mortality rate for emergency urological surgery of 18% is more in keeping with data published in 2011 on emergency non-trauma surgery in nonagenarians, where the inhospital mortality rate was 29% for general, vascular and urological surgery combined. 4 Of the 102 operations carried out, 11 were for urological problems and 5 (45%) of these patients died postoperatively. When analysing outcomes of elective procedures, we face the inherent bias of patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Pelavski et al reported a 29% in-hospital mortality rate after emergency non-trauma surgery in nonagenarians. 4 In another study looking at 1,063 surgical procedures in nonagenarians, 84 elective urological procedures were performed with a 30-day mortality rate of 3.6%. 5 Additionally, non-operative emergency management of elderly patients consumes significant medical resources.…”
mentioning
confidence: 99%